PERUBAHAN MEDIA KOMUNIKASI DALAM POLA KOMUNIKASI KELUARGA DI ERA DIGITAL: Ditha Prasanti - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2016)
The development of today's digital information age has changed the changes in the communication media used in a family portrait. Family harmony, as a source of information and early socialization has shifted into a digital family, children become digital native, and adults into a digital immigrant. In this study, researchers took the object of study using purposive sampling techniques, the family who lived in Bandung, the active use of digital communication media. Face-to-face interaction and communication is now taken over by the communication mediated by information technology, and is clean in virtual culture. Communication theory suitable for use in this article is the theory of technological determinism. The research approach used in this study is a qualitative approach with descriptive methods. Data collection techniques used were observation, interviews, and documentation. The results showed that the technological development has resulted in a change of communications media in the digital family communication patterns. Changes of this communications medium has created a solitary man (homo-solitarius). Family communication is happening for families who use information technology in the digital age has produced a model of life based on the principles of individualism and economism has created a model of life lonely in a crowd.